Make in India: Success and Challenges - A Study - Dr P.M.Murali (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Launched in 2014, Make in India aimed to transform India into a global manufacturing hub. This study evaluates the initiative’s success and challenges, analyzing policy frameworks, sectoral growth, and investment trends. Results show significant improvements in ease of doing business, foreign direct investment (FDI) inflows, and job creation. However, challenges persist, including infrastructure constraints, skill gaps, and bureaucratic hurdles. The study recommends policy refinements, infrastructure development, and skill enhancement to sustain growth.